Digital Fatigue and Psychological Well-Being among Generation Z Students - Asultoni Imam Hidayat; Farhan Farhan (Pattimura Proceeding, 2026)
The swift progression of digital advancements has profoundly reshaped how Generation Z students live, as they depend considerably on digital tools for both their schoolwork and connecting with others. Yet, using these tools too much often causes digital weariness, a state marked by feeling physically and mentally drained from looking at screens for too long. This research investigates how digital weariness affects the mental health and overall psychological state of Generation Z students by deeply examining personal stories. We talked to five students who use digital devices for a minimum of six hours each day and carefully studied the information gathered using the Creswell and Poth method. The discoveries indicate that digital weariness causes issues like sore eyes, trouble focusing, feeling uninterested in things online, and problems sleeping, all of which make stress and worry worse and decrease the desire to learn. On an emotional level, it lessens joy and hurts relationships with friends and family. These outcomes emphasize how crucial it is to use digital tools in a healthy way and handle time wisely to protect students' mental health.